1989
DOI: 10.1159/000461033
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Poor Platelet Concentrates at the Bedside by Filtration through Sepacell-PL

Abstract: We developed a new filter, ‘Sepacell-PL’, consisting of a blood administraiton set for the preparation of leukocyte-poor platelet concentrates at the patient’s bedside. This filter is packed with 1.8 pm polyester fibers coated with a new polymer, and has a volume of 14 ml. Sepacell-PL removed more than 99% of the leukocytes while approximately 93% of platelets were recovered from 10 units of platelet concentrates which contained 5 x 10^8 leukocytes and 3 x 10^11 platelets. The functions of pre- and postfiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…However, again no differences between the filtered pooled PC and the unfiltered control pool in the expression of activation antigens, platelet aggregation, platelet adhesion to collagen in flowing blood, platelet nucleotide content or nucleobase release, platelet morphology or platelet glucose consumption and lactate production were found. This is in agreement with other studies in which no effect of filtration on various in vitro and in vivo parameters of platelets prepared by the PRP method was found [11][12][13][14], however in these studies PC were not stored after filtration. Depletion of leukocytes from PC might also improve the quality of platelets during storage because leukocytes have a detrimental effect on platelets during storage [31, 321. However, no positive effect of leukocyte reduction on platelet function was observed, as was found also for the BC-PC (with a 10-fold lower initial leukocyte contamination).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, again no differences between the filtered pooled PC and the unfiltered control pool in the expression of activation antigens, platelet aggregation, platelet adhesion to collagen in flowing blood, platelet nucleotide content or nucleobase release, platelet morphology or platelet glucose consumption and lactate production were found. This is in agreement with other studies in which no effect of filtration on various in vitro and in vivo parameters of platelets prepared by the PRP method was found [11][12][13][14], however in these studies PC were not stored after filtration. Depletion of leukocytes from PC might also improve the quality of platelets during storage because leukocytes have a detrimental effect on platelets during storage [31, 321. However, no positive effect of leukocyte reduction on platelet function was observed, as was found also for the BC-PC (with a 10-fold lower initial leukocyte contamination).…”
Section: Discussionsupporting
confidence: 92%
“…The more activated state of platelets prepared by the PRP method may also influence the effect of filtration on the in vitro platelet function during long-term storage after filtration. N o effect of filtration on platelet function and activation was found before [I [1][2][3][4][5][6][7][8][9][10][11][12][13][14], but it was found that after filtration the percentage platelets expressing CD62 was reduced [ 151.…”
Section: Introductionmentioning
confidence: 99%
“…MPV was significantly reduced following filtration, which suggests that the filters can selectively remove larger platelets. Similar results were reported by Miyamoto et al [18]; these findings can be considered a disadvantage, based on data indicating that larger platelets are younger and more effective, or an advantage, based on the opposite evidence that larger platelets are older and less hemostatically effective [20]. The results of studies concerning platelet membrane expression of constituents associated to platelet activation (GMP 140 and gp 53) [7] and postransfusion recovery and survival (GMP 140 and glycoprotein Ib) [4, 61 indicate that filtration through these filters does not induce important modifications of the variables examined.…”
Section: Discussionsupporting
confidence: 92%
“…Cell separation is a key process involved in leukocyte removal from blood cells for transfusion [1][2][3][4][5] and isolation of stem cells from peripheral and umbilical cord blood. 6,7 Polyurethane foam membranes [1][2][3]6,7 and nonwoven fabrics, 4 with pore sizes of 5-20 m, have been used as separation membranes for blood cells.…”
Section: Introductionmentioning
confidence: 99%